Simulation of Dispersion Potential and Fatality Percentage of SO2 and CO2 Flue Gas from Combustion of Coal in West Lombok Power Plant using Gaussian Model - Shafwan Amrullah; Cyrilla Oktaviananda (CHEMICA: Jurnal Teknik Kimia, 2020)
Combustion of coal in coal-fired power plants produces air pollution such as SO2, NOx, CO2, and Particulates. The Jeranjang power plant in West Lombok Regency uses 300,000 tons/year of coal to generate 75 MW of electricity. It can be a large potential for environmental pollution. This research aims to simulate the potential of SO2 and CO2 exhaust gas dispersion to the environment and the fatality percentage caused by burning the Jeranjang coal power plant using the Gauss Model. The research was conducted by a literature study and direct observation of PLTU Jeranjang. After that, in this research, the SO2 and CO2 concentration were calculated. At the end of the study, estimating the potential dispersion and fatality percentage by SO2 and CO2 gas was also calculated around the Jeranjang power plant. The results are SO2 dispersion with a dispersion mass of 0.145 kg/sec from a distance of 2,000 to 46,000 m increased from 1x10-45 to 1.9x10-5 ppm and decreased to 0 ppm. The fatality percentage generated is 0%. The CO2 dispersion potential into the environment without a mass of 12.378 kg/sec increases at a distance of 2,000 to 58,000 m, from a concentration of 2.7x10-65 to 0.00184 ppm. The CO2 concentration decreases to 0 ppm. The fatality percentage generated is 0%. The calculation of settlement dispersion around the PLTU Jeranjang can be safe from SO2 and CO2 dispersion, and the fatality percentage generated is 0%.